Cost Analysis Based On Unit Costs In Inpatient Rooms At Cendrawasih Regional General Hospital, Dobo, Maluku Province (Journal of Namibian Studies : History Politics Culture, 2023)
The calculation for setting the hospital rate based on the unit cost component is the result of calculating the total cost of each activity incurred by the hospital which is then divided by the total output at each cost center. The purpose of this study was to determine the cost analysis based on the unit cost at the Inpatient Installation of the Cendrawasih Dobo General Hospital, Maluku Province. This research is a quantitative research using the descriptive survey method. The population in this study is all financial transactions that occur at the Cendrawasih Regional General Hospital in Dobo in 2022. The sample is all financial transactions related to fixed costs, variable operational costs, and fixed operational costs incurred at the inpatient installation of the Cendrawasih Regional General Hospital. Dobo in 2022. The results of this study show that the rate based on unit costs is obtained for VIP class inpatient care of Rp.248,919, -, Class 1 of Rp.154,778, -, Class 2 of Rp.115,799, - and Class 3 of Rp.83,362,-. Suggestions for hospitals need to consider unit cost analysis, patient's ability, and willingness to pay as material for scientific consideration to determine rational rates that are balanced between the interests of the hospital and the needs and abilities of the people of Maluku Province.